2023
DOI: 10.1002/adma.202211406
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of In‐Memory Computing in a Ferrofluid System

Abstract: Magnetic fluids are excellent candidates for several important research fields including energy harvesting, biomedical applications, soft robotics, and exploration. However, notwithstanding relevant advancements such as shape reconfigurability, that have been demonstrated, there is no evidence for their computing capability, including the emulation of synaptic functions, which requires complex non‐linear dynamics. Here, it is experimentally demonstrated that a Fe3O4 water‐based ferrofluid (FF) can perform elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our experiments conducted in controlled laboratory conditions also revealed the potential of ZnO colloid mixtures to function as electrical analogue neurons, successfully implementing synaptic-like learning as described in [ 10 , 11 ], as well as demonstrating the manifestation of Pavlovian reflexes [ 12 ]. The experimental study presented in [ 13 ] showcases the classification capabilities of a Fe 3 O 4 water-based ferrofluid for digit recognition within an 8 8-pixel dataset. Additionally, we demonstrated that this ferrofluid could be programmed using quasi-direct current signals and read in radio frequency mode.…”
Section: Introductionmentioning
confidence: 99%

Logical circuits in colloids

Roberts,
Raeisi Kheirabadi,
Tsompanas
et al. 2024
R. Soc. Open Sci.
Self Cite
“…Our experiments conducted in controlled laboratory conditions also revealed the potential of ZnO colloid mixtures to function as electrical analogue neurons, successfully implementing synaptic-like learning as described in [ 10 , 11 ], as well as demonstrating the manifestation of Pavlovian reflexes [ 12 ]. The experimental study presented in [ 13 ] showcases the classification capabilities of a Fe 3 O 4 water-based ferrofluid for digit recognition within an 8 8-pixel dataset. Additionally, we demonstrated that this ferrofluid could be programmed using quasi-direct current signals and read in radio frequency mode.…”
Section: Introductionmentioning
confidence: 99%

Logical circuits in colloids

Roberts,
Raeisi Kheirabadi,
Tsompanas
et al. 2024
R. Soc. Open Sci.
Self Cite
“…Researchers have demonstrated movement and manipulation of a liquid cluster based on ferrofluids [2][3][4] and liquid metals [5][6][7][8][9] . Furthermore, ferrofluids have also been reported to enable in-memory computation 10 . These robotic systems usually move by applying external electromagnetic fields.…”
mentioning
confidence: 99%